Managing Thrips and Tomato Spotted Wilt in Pepper - Joe Funderburk; Steve Olson; Julianne Stavisky; Yolanda Avila (EDIS)
Thrips are serious pests of ornamental, vegetable, and fruit crops in the field and greenhouse. Feeding and egg-laying by thrips results in distortion, discoloration, silvering, and bronzing of leaves and fruits of vegetables reducing their market value. Some species of thrips are vectors of bunyaviruses (family Bunyaviridae, genus Tospovirus, type species Tomato spotted wilt). Severe epidemics occur annually on food, fiber, and ornamental crops in temperate, subtropical and tropical regions of the world. This document is ENY-658, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Date printed: March 2004.